AKAUNTABILITI PENGKAJI KAJIAN KES BERKAITAN PENGAJARAN GURU PENDIDIKAN ISLAM DALAM MENGINTEGRASIKAN KEMAHIRAN BERFIKIR ARAS TINGGI (KBAT): Accountability Researchers of Case Study Related to the Teaching of Islamic Education Teachers in Integration of Higher Order Thinking Skills (HOTS) - Mohd Zeki, Mohd Zaidi; Mazlan, Nurul Hijja; Talib, Nor Zanariah; Mat Jusoh, Ahmad Muhaimin; Moshidi, Nurulaini (Journal of Islamic Educational Research, 2023)
This study was conducted through a qualitative case study approach to explore the problems related to the integration of HOTS in the teaching of secondary school Islamic studies. Since trustworthiness in qualitative research is an important aspect to justify the validity and reliability of the research, researcher reflexivity plays an important role in the overall data collection and analysis process. This research illustrates the importance of accountability in qualitative research. Apart from the knowledge of educational research philosophy, the study contributes to a greater understanding of how it is designed, including the data management, data collection and data analysis procedures.